STABILITY INDICATING VALIDATED HPLC METHOD FOR THE DETERMINATION OF ZANUBRUTINIB IN BULK AND PHARMACEUTICAL DOSAGE FORM - KUMARI, M. VIJAYA; REDDY, CH. BALASEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: An accurate, rapid economical and straight forward, reliable assay technique was evolved and showed for the evaluation of zanubrutinib using reversed-phase high-performance liquid chromatography. Methods: In the proposed method, efficient chromatographic separation was achieved applying acetonitrile and 0.1% orthophosphoric acid (50:50 v/v) as a mobile phase with a flow of 1 ml/min and the wavelength was observed at 220 nm. Chromatography was administered isocratically at ambient temperature and run time was approximately 6 min and the retention time (Rt) was observed as 4.358 min. Results: The method was justified as per ICH guidelines. System suitability parameters were studied by injecting the quality six fold and results were well under acceptance criteria. Linearity study was administered between 10% and 150% levels, regression coefficient value was observed as 0.999. Limit of detection and limit of quantification were observed as 0.02 μg/ml and 0.2 μg/ml, respectively. Precision was found to be 0.74 for repeatability and 0.68 for intermediate precision. Recovery of the drug was found to be 98–102%, indicates that the recovery is in the acceptable limit. Validation results were found to be satisfactory and the method applicable for bulk and formulation analysis. Hence, it was evident that the proposed method was said to be suitable for regular analysis and quality control of pharmaceutical preparations. Conclusion: The validation results were in good agreement with the acceptable limit. Relative standard deviation values which are <2.0% indicating the accuracy and precision of this method. Assay of retail formulation was administered and found to be 100.24% was present using the above method. Stress conditions of degradation in acidic, alkaline, peroxide, and thermal were studied. This developed method showed reliable, precise, accurate results under optimized conditions.